2019
DOI: 10.1167/iovs.19-27306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Epigallocatechin Gallate of IL-1–Induced Urokinase-Type Plasminogen Activator Expression and Collagen Degradation by Corneal Fibroblasts

Abstract: Citation: Sugioka K, Yoshida K, Murakami J, et al. Inhibition by epigallocatechin gallate of IL-1-induced urokinase-type plasminogen activator expression and collagen degradation by corneal fibroblasts. Invest Ophthalmol Vis Sci. 2019;60:2895-2903.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These cytokines are responsible for activating the expression of pro-inflammatory mediators during chronic inflammation. It has been demonstrated that IL1B induces the expression of PLAUR, gene encoding the urokinase plasminogen activator receptor (uPAR), and PLAU (urokinase plasminogen activator; uPA) ( 36 , 37 ). Both PLAUR and PLAU are upregulated in pJIA.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are responsible for activating the expression of pro-inflammatory mediators during chronic inflammation. It has been demonstrated that IL1B induces the expression of PLAUR, gene encoding the urokinase plasminogen activator receptor (uPAR), and PLAU (urokinase plasminogen activator; uPA) ( 36 , 37 ). Both PLAUR and PLAU are upregulated in pJIA.…”
Section: Discussionmentioning
confidence: 99%
“…Human corneal fibroblast cells were cultured in a three-dimensional (3D) collagen gel which was treated by EGCG. The study showed that EGCG can inhibit the inflammatory factor IL-1β, leading to the reduction of urokinase-type plasminogen activators in corneal fibroblasts [ 76 ].…”
Section: Therapeutic Uses In Eye Diseasesmentioning
confidence: 99%
“…As a result, EGCG requires additional research as a potential therapy for corneal ulcer. [ 76 ] in-vivo rat glaucoma EGCG (50 mg/kg/day) The NF-κB signaling pathway is involved in the anti-inflammatory impact of EGCG. [ 85 ] in-vivo rat retinal ganglion cells glaucoma GTE (275 mg/kg) To summarize, under ischemic conditions, GTE provides neuroprotection to retinal ganglion cells, which proposes a prospective therapeutic approach for the treatment of glaucoma and optic neuropathies.…”
Section: Therapeutic Uses In Eye Diseasesmentioning
confidence: 99%
“…To study corneal ulcer, proinflammatory cytokine IL-1β is able to induced corneal collagen degradation ( 109 ). In IL-1β treated three-dimensional (3D) cultured human corneal fibroblast, EGCG treatment could suppress collagen degradation in a concentration-dependent manner ( 110 ). EGCG was found to suppressed the conversion of exogenous plasminogen to plasmin induced by IL-1β, leading to the inactivation of pro-MMP1.…”
Section: Anti-inflammatory Effects Of Gte In Eye Diseasesmentioning
confidence: 99%